Primary cardiac angiosarcoma directly invading the right lung: An autopsy report - Takumi Kiwaki; Akira Ishihara; Takanori Toyama; Hiroaki Kusaka; Hiroaki Kataoka (Clinical Case Reports, 2021)
Abstract We presented a difficult‐to‐diagnose case of cardiac angiosarcoma. The patient presented pericardial effusion, but cytology of the effusion was negative. Because cytological detection of angiosarcoma cells is difficult, a possibility of malignancy should not be excluded with negative cytological examination. Biopsy of cardiac mass is the best way for diagnosis.